Perbedaan Kekerasan Resin Modified Glass Ionomer Cement dan Kompomer pada Pengguna Obat Kumur Alkohol dan Non Alkohol - Nia Wijayanti; Desi Lia Avisa Dwi Hartoyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
The restoration materials, Resin Modified Glass Ionomer Cement and compomer, often contact with various kinds of liquid in oral cavity. One of the liquid which has contact in oral cavity was mouthwash. The effect of using mouthwash can affect the hardness of the material. Hardness affects the longevity of a filling material persisted in the oral cavity. This study aims to determine the difference in hardness between Resin Modified Glass Ionomer Cement and compomers on the users of alcohol and non alcoholic mouthwash. The type of the research is quasi experimental. There are 36 samples (18 RMGIC and 18 compomers). Each ingredient was divided into two groups which were immersed in alcoholic and non alcoholic mouthwashes. Then, the samples were immersed for 5 days which were replaced every 24 hours. The sample hardness was measured by the Vickers Hardness Test (Shimadzu HMV-M3). Data were analyzed using the Kruskal Wallis test. After being tested, the average results of the non alcohol compomer hardness were 31.89, 22.94 alcoholic compomers, 14.17 non alcoholic RMGIC, and 5.00 alcoholic RMGICs. The Kruskal Wallis analysis test results obtained p value <0.5 showed there is a significant difference. There is a significant differencein the hardness of the Resin Modified Glass Ionomer Cement (RMGIC) and the compomer on the users of alcohol and non alcoholic mouthwash. The hardness from highest to lowest is compomers immersed in non alcoholic mouthwash, compomers in alcoholic mouthwash, RMGIC in non alcoholic mouthwash, and RMGICs in alcoholic mouthwash.